WEAR BEHAVIOR OF AZ91D MAGNESIUM COMPOSITE - Erarslan, Yaman; Akca, Cem (YILDIZ TECHNICAL UNIV, 2015)
AZ91D alloy was produced using the conventional casting methods in a local foundry. Then, SiC ceramic additive materials (particulates) with 2%, 4% and 8% by weight (average grain size of 7 mu m and 32 ae m) were mixed with AZ91 alloy by stir-casting method. The properties of the AZ91 alloy and AZ91/SiC composite materials produced were determined by means of hardness and wear tests, and microstructural characterization was conducted by optical microscopy, scanning electron microscopy and x-ray diffraction. It was observed that the improvement in hardness for the composite with a diameter of 7 ae m diameter is higher than the composite with a diameter of 32 ae m. Wear testing was conducted through the ball-on-disc method at a rate of 10 cm.s(-1) under a load of 5 N. The friction coefficient was found to be between the 0.115-0.172 intervals, and no wear was observed on the alumina (Al2O3) ball material.
Keywords: AZ91 alloy; metal matrix composite; wear; Engineering